AB0224 Difficulty in Maintaining Full Physical Function for 10 Years in Patients with Early Rheumatoid Arthritis in Daily Clinical Practice. Analysis of the Iorra Cohort. (10th June 2014) - Nakajima, A.; Inoue, E.; Shimizu, Y.; Kobayashi, A.; Shidara, K.; Seto, Y.; Hoshi, D.; Sugimoto, N.; Tanaka, E.; Taniguchi, A.; Momohara, S.; Yamanaka, H.
Abstract : Background: Dramatic improvement of immunosuppressive and biological treatment for rheumatoid arthritis (RA) is thought to be widespread in daily clinical practice in the past 10 years. Whether this improvement has brought the same benefit to patients with established RA as with early RA has not yet been elucidated. Objectives: To investigate the changes in disease activity and physical function in 10 years in patients with early RA and established RA in daily practice. Methods: Patients with early RA (disease duration <2 years) and established RA (disease duration 10–12 years) at the IORRA surveys in April or October 2002 conducted at Tokyo Women's Medical University were selected and followed for 10 years. Changes in disease activity by the 28-joints disease activity score (DAS28) and in physical function by the Japanese version of the Health Assessment Questionnaire (J-HAQ) were assessed every 6 months by using mixed-model analysis (MM).The average doses of methotrexate and prednisolone were calculated; the analysis included patients who did not use them. Treatment intensity was evaluated with increase in methotrexate dose or administration of biologics from the time of the start of this observation. Risk factors for being lost to follow-up over the past 10 years were analyzed separately in the early RA group and the established RA group with a Cox regression model. Results: The early RA group contained 336 patients (77.7% female) with a mean (±SD) age of 55.3±15.3 years. The established RA group contained 575 patients (81.3% female) with a mean (±SD) age of 58.4±12.3 years. The DAS28 gradually decreased from 3.6 to 2.8 in the early RA group and from 3.8 to 3.1 in the established RA group. The mean (±SD) doses of methotrexate continually increased both in the early RA group (from 1.7 to 5.8 [±1.6] mg/week) and the established RA group (from 3.1 to 4.3 [±1.7] mg/week). The duration from the start of observation until either an increase in methotrexate dose or administration of biologics was shorter in the early RA group than in the established RA group (p=0.068). The doses of prednisolone decreased both in the early RA group (from 2.3 to 0.7 mg/day) and in the established RA group (from 2.4 to 1.8 mg/day). The J-HAQ in the early RA group improved slightly from 0.57 to 0.48 over 5 years then deteriorated slightly after that to 0.53 (±0.825), whereas that of the established RA group steadily deteriorated from 0.79 to 0.91 (±0.99). Over 10 years, 204 (60.7%) patients were lost to follow-up, with at least 29 deaths (8.6%) in the early RA group, and 333 (58.4%) patients were lost to follow-up with at least 73 deaths (12.7%) in the established RA group. Risk factors associated with being lost to follow-up were older age (hazard ratio [HR] 1.02, p<0.001 in the early RA group; HR 1.03, p<0.001 in the established RA group), and baseline J-HAQ=0 in the early RA group (HR 1.52, p<0.05) and baseline J-HAQ>1.25 in the established RA group (HR 1.55, p<0.01) compared to 0<J-HAQ≤0.5. Conclusions: Even in patients with early RA, it is difficult to maintain physical function in daily practice. This study revealed the difficulty of integrating the new treatment strategy into daily practice. Disclosure of Interest: A. Nakajima: None declared, E. Inoue: None declared, Y. Shimizu: None declared, A. Kobayashi: None declared, K. Shidara: None declared, Y. Seto: None declared, D. Hoshi: None declared, N. Sugimoto: None declared, E. Tanaka: None declared, A. Taniguchi: None declared, S. Momohara Speakers bureau: Abbott, AbbVie, Astellas, Bristol-Myers Squib, Chugai, Eisai, Mitsubishi Tanabe, Pfizer, Takeda, Teijin, H. Yamanaka Grant/research support: Abbott, AbbVie, Asahikasei, Astellas, AstraZeneca, Bristol-Myers Squib, Chugai, Daiichi Sankyo, Eisai, GlaxoSmithKline, Janssen, Mitsubishi Tanabe, MSD, Nippon Kayaku, Pfizer, Santen, Taishotoyama, Takeda, Teijin, Consultant for: Abbott, AbbVie, Astellas, AstraZeneca, Bristol-Myers Squib, Chugai, Daiichi Sankyo, Eisai, Mitsubishi Tanabe, Nippon Kayaku, Pfizer, Takeda, Teijin, Speakers bureau: Abbott, AbbVie, Astellas, Bristol-Myers Squib, Chugai, Eisai, Mitsubishi Tanabe, Pfizer, Takeda, Teijin, DOI: 10.1136/annrheumdis-2014-eular.2124